Does macroeconomic performance leads to human development: An empirical evidence from Asian economies - Sami Ullah; Parvez Azim; Rana Ejaz Ali Khan (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The main objective of this study is to empirically investigate whether economic performance in Asian economies is helpful for human development or not. For this purpose, data of 40 Asian economies has been taken from various international sources. Empirical investigation has been done by two-stage least square and validity of estimations have been verified by various diagnostic tests. The analysis has been divided into three parts, i.e. for overall Asian economies, economies with high HDI (above the median HDI) and economies with low HDI (below the median HDI). Results show that credit to private sector and urbanization are the most important and influential macroeconomic indicators for promotion of human development (overall economies, high HDI economies and low HDI economies). Capital formation contributed in human development only in overall economies. The performance of monetary and fiscal sectors proxied by supply of M2 and collection of taxes respectively are not leading to human development but results show that monetary indicator is negatively influencing human development in overall analysis of Asian countries as well as high HDI and low HDI economies. However fiscal indicator has shown insignificant effect in overall economies, positive effect in above the median economies and negative effect in below the median economies.
Keywords: 330; capital formation; quality of life; urbanization; monetary policy; fiscal policy